Step revision in hybrid Co-simulation with FMI - Cremona, Fabio; Lohstroh, Marten; Broman, David; Di Natale, Marco; Lee, Edward A.; Tripakis, Stavros (2016 ACM/IEEE International Conference on Formal Methods and Models for System Design (MEMOCODE), 2016)
This paper presents a master algorithm for co-simulation of hybrid systems using the Functional Mock-up Interface (FMI) standard. Our algorithm introduces step revision to achieve an accurate and precise handling of mixtures of continuous-time and discrete-event signals, particularly in the situation where components are unable to accurately extrapolate their input. Step revision provides an efficient means to respect the error bounds of numerical approximation algorithms that operate inside co-simulated FMUs. We first explain the most fundamental issues associated with hybrid co-simulation and analyze them in the framework of FMI. We demonstrate the necessity for step revision to address some of these issues and formally describe a master algorithm that supports it. Finally, we present experimental results obtained through our reference implementation that is part of our publicly available open-source toolchain called FIDE.